Pengaruh NPL Dan CAR Terhadap Profitabilitas Dengan Restrukturisasi Kredit Sebagai Variabel Moderasi Pada Sektor Perbankan - luh putu sulastrini; I Putu Gede Diatmika; I Gusti Ayu Purnamawati (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2023)
Abstract The global financial recession that occurred due to the widespread Covid-19 outbreak since the end of 2019, became one of the phenomena that was able to reduce the stamina of the national economy, one of the sectors affected was the banking sector. This study aims to examine and analyze the effect of Non Performing Loans (NPL) on Profitability, the effect of Capital Adequacy Ratio (CAR) on Profitability, the effect of credit restructuring in moderating the effect of NPL on Profitability, the effect of credit restructuring in moderating the effect of CAR on Profitability. The data analyzed is secondary data based on banking financial statements listed on the IDX dated December 31, 2017, 2018, 2019, and 2020. The analytical method used is Moderated Regression Analysis using the SPSS 21 program. The results show that NPL has a significant influence on profitability, CAR has a significant effect on profitability, credit restructuring is able to moderate the effect of NPL on profitability and credit restructuring is not able to moderate the effect of CAR on profitability.   Keywords: NPL, CAR, Profitability, Credit Restructuring, Banking Sector.